LITERARY ANALYSIS OF THE DEPICTION OF THE IMAGE OF AMIR TEMUR IN “THE FAREWELL OF MOTHER HAWK” WRITTEN BY PIRIMKUL KADYROV (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the depiction of the image of Amir Temur in “The farewell of mother hawk” written by Pirimkul Kadyrov and analyses the correlation of real facts and imagination with examples.